Integração do mercado de alho de no estado de Minas Gerais - Mattoso, Marcos Joaquim; Martins Rezende, Alberto; Aad Neto, Alexandre; Fagundes de Sousa, Antônio; Brandt, Sérgio Alberto (Revista Ceres, 2025)
Knowledge of inter-regional prices and market interatins can be used to orient policiesof road construction and repair. The objective of this study is to estimate the degree of market integration of garlic in the state of Minas Gerais.